1986
DOI: 10.1002/fut.3990060412
|View full text |Cite
|
Sign up to set email alerts
|

A note on agricultural options and the variance of futures prices

Abstract: he recent introduction of options on agricultural futures has fueled a growing T research interest on issues ranging from risk-return characteristics of option hedging strategies to the valuation of commodity options. Valuation models for options on common stocks have been extensively used ever since Black and Scholes published their seminal paper in 1972. However, direct application of the traditional option pricing models in evaluating agricultural futures options may not be appropriate, especially if the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Anderson (1985); and Milonas and Vora (1985), found that price volatilities of agricultural commodity prices are nonstationary. First, there is a month effect.…”
Section: Methodology and Statistical Testsmentioning
confidence: 98%
See 1 more Smart Citation
“…Anderson (1985); and Milonas and Vora (1985), found that price volatilities of agricultural commodity prices are nonstationary. First, there is a month effect.…”
Section: Methodology and Statistical Testsmentioning
confidence: 98%
“…Such a monotonic effect will bias the results unless proper measures are taken. Milonas and Vora (1985) presented evidence that futures prices in agricultural commodities, maturing in different months behave differently. An old crop contract is expected to exhibit higher variability than a new crop contract.…”
Section: Data and Statistical Considerationsmentioning
confidence: 98%